Estudio del fósforo en suelos de América Central. V. Uso de resinas de intercambio para evaluar la disponibilidad de P - Palma, G.; FASSBENDER, H.W. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The objective of this study was to evaluate the use anion exchange resin (Dowex 21K) as an index of P availability in 40 soils of Central America. The following determinations were undertaken, according to Cooke: 1. Initially available -kinetic- P (shaken 2 to 30 minutes) 2. Equilibration -intensity- P (shaken 18 hours) 3. Reserve -capacity- P (five successive extractions) The kinetical criteria used to evaluate the dynamics of P during the first 30 minutes of contact of the soils with the resin indicated that P initially available is not a good index of measure the P absorbed by the plant. For a group of 40 soils considered, the correlation between P adsorbed by the resin during 18 hours equlibration and the P absorbed by the tomato plants was 0.930, the correlation between reserve P measured by five successive equilibrations and absorbed P by tha plants was 0.951. It was concluded that equilibration P and reserve P are the most significant parameters to evaluate that availability of P in the soils. Higher correlations obtained for the resin method as compared with other chemical procedures indicated that resin is better for the evaluation of P available in the soil.